Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) - Silva, Ana Catarina (Henry Stewart Talks, 2023)
Introduction to the nanosystems, Definition of lipid nanoparticles, Types of lipid nanoparticles, Solid lipid nanoparticles (SLN), Nanostructured lipid carriers (NLC), SLN and NLC production methods, Examples of applications: cutaneous use and nose-to-brain route